Racial Disparities in Above‐knee Amputations After TKA: A National Database Study. Issue 7 (July 2017) - George, Jaiben; Navale, Suparna M.; Schiltz, Nicholas K.; Siccha, Miguel; Klika, Alison K.; Higuera, Carlos A.
Abstract: Background: Above‐knee amputation (AKA) is a rare but devastating complication of TKA. Although racial disparities have been previously reported in the utilization of TKA, it is unclear whether disparities exist in the rates of AKA after TKA. Questions/purposes: (1) Which gender‐racial group has the highest rate of AKA from septic and aseptic complications of TKA? (2) Which age groups have higher rates of AKA from septic and aseptic complications of TKA? Methods: Using National Inpatient Sample data from 2000 to 2011, AKAs resulting from complications of TKA were identified using a combination of International Classification of Diseases, 9th Revision procedure and diagnosis codes. Of the 341, 954 AKAs identified, 9733 AKAs were the result of complications of TKA (septic complications = 8104, aseptic complications = 1629). Standardized AKA rates were calculated for different age and gender‐ racial groups by dividing the number of AKAs in each group with the corresponding number of TKAs. Standardized rate ratios were calculated after adjusting for demographics and comorbidities. Results: After adjusting for age and comorbidities, black men had the highest rate of AKA after TKA (adjusted rate in black men = 578 AKAs per 100, 000 TKAs, standardized rate ratio [SRR] = 4.32 [confidence interval CI, 3.87‐4.82], p < 0.001). Black men also had the highest rate of AKA after septic complications of TKA (p < 0.001). The adjusted rates of AKA were higher in patients younger than 50 years (adjusted rate = 473, SRR = 3.14 [CI, 2.94‐3.36], p < 0.001) and older than 80 years (adjusted rate = 297, SRR = 1.85 [CI, 1.76‐1.95], p < 0.001). Conclusions: The rising demand for TKA has led to an increase in the number of AKAs performed for complications of TKA in the United States. Although we did not find an increase in the rate of AKA during the study period, certain populations, including black men and patients older than 80 years and younger than 50 years, had higher rates of AKA. Further studies are required to understand the reasons for these disparities and measures should be undertaken to eliminate these disparities. Level of Evidence: Level III, therapeutic study.